The Analysis Between Batak Toba and English In Question Words - Ade Armando; Danny Boy Damanik; Surya Ningsih Pakpahan; Ravika Siregar; Anita Sitanggang (CV Putra Publisher, 2023)
The purpose of this research is to identify the similarities and differences between English and Toba Batak question terms. Qualitative descriptive research method. Methods of data collection including documentation. Descriptive analysis is used by researchers to examine the data. There are 5 question words in English: